Medical costs and utilization in patients with depression treated with adjunctive atypical antipsychotic therapy - Nadkarni, Anagha (Dove Medical Press, 2013)
OBJECTIVE: To compare total medical costs and utilization over a 12-month period in commercially insured patients receiving FDA-approved adjunctive atypical antipsychotics (aripiprazole, olanzapine, or quetiapine) for depression. METHODS: A retrospective claims analysis was conducted from 2005–2010 using the PharMetrics database. Subjects were adult commercial health-plan members with depression, identified using International Classification of Diseases codes and followed for 12 months after augmentation with an atypical antipsychotic. Outcomes included total medical costs, hospitalization, and ER visits. Generalized linear models and logistic regression were used to compare the total medical costs and the odds of hospitalization and ER visits between the treatment groups after adjusting for baseline demographic and clinical characteristics. RESULTS: A total of 9675 patients with depression were included in the analysis, of which 68.4% were female, with a mean age of 45.2 (±12.0) years. Adjusted 12-month total medical costs were higher for olanzapine ($14,275) and quetiapine ($12,998) compared to aripiprazole ($9,801; P < 0.05 for all comparisons with aripiprazole). When divided into inpatient and outpatient costs, olanzapine and quetiapine had significantly higher adjusted inpatient costs compared to aripiprazole ($6,124 and $4,538 vs $2,976, respectively; P < 0.05 for all comparisons with aripiprazole). Similar results were seen for adjusted outpatient costs. Adjusted odds of hospitalization for olanzapine (odds ratio [OR] = 1.73; 95% CI confidence interval [CI] = 1.42–2.10) and quetiapine (OR = 1.40; 95% CI = 1.21–1.60) were significantly higher than aripiprazole at 12 months. The adjusted odds of an ER visit for olanzapine (OR = 1.40; 95% CI = 1.18–1.65) and quetiapine (OR = 1.62; 95% CI = 1.44–1.81) were also significantly higher compared to aripiprazole at 12 months. CONCLUSIONS: In commercially insured major depressive disorder patients, olanzapine and quetiapine were associated with higher total medical costs, the difference being primarily attributable to higher inpatient costs. Additionally, olanzapine and quetiapine were associated with significantly higher odds of hospitalization and ER visits compared to aripiprazole.